Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Jasa Warnet Nadiputra Di Denpasar - Yasa, Kadek Adi Saputra; Ardani, I Gusti Agung Ketut Sri (E-Jurnal Manajemen, 2014)
In an era when this information is needed by various parties. The main characteristic that marks the beginning of the information age is the internet. Figuring NadiPutra services as one of the business internet services in West Denpasar, and business services figuring NadiPutra not escape from competition from other Internet service business in the city of Denpasar West in particular. The variables studied were the quality of service to customer satisfaction. The number of samples used by purposive sampling technique was 105 respondents. The results of the analysis of data with multiple linear regression analysis techniques show that: 1) Quality of service consisting of tangible, reliability, responsiveness, assurance, and empathy simultaneously positive and significant effect on customer satisfaction figuring NadiPutra Services in West Denpasar. 2) Quality of service consisting of tangible, reliability, responsiveness, assurance, and empathy partially positive and significant effect on customer satisfaction figuring NadiPutra Services in West Denpasar. Keywords: quality of service, customer satisfaction